Mandibular advancement oral appliance therapy for obstructive sleep apnoea: effect on awake calibre of the velopharynx. Issue 11 (1st November 1999) - Ryan, C F; Love, L L; Peat, D; Fleetham, J A; Lowe, A A
Abstract : BACKGROUND: The mechanisms of action of oral appliance therapy in obstructive sleep apnoea are poorly understood. Videoendoscopy of the upper airway was used during wakefulness to examine whether the changes in pharyngeal dimensions produced by a mandibular advancement oral appliance are related to the improvement in the severity of obstructive sleep apnoea. METHODS: Fifteen patients with mild to moderate obstructive sleep apnoea (median (range) apnoea index (AI) 4(0–38)/h, apnoea-hypopnoea index (AHI) 28(9–45)/h) underwent overnight polysomnography and imaging of the upper airway before and after insertion of the oral appliance. Images were obtained in the hypopharynx, oropharynx, and velopharynx at end tidal expiration during quiet nasal breathing in the supine position. The cross sectional area and diameters of the upper airway were measured using image processing software with an intraluminal catheter as a linear calibration. RESULTS: AI decreased to a median (range) value of 0 (0–6)/h (p<0.01) and AHI to 8 (1–28)/h (p<0.001) following insertion of the oral appliance. The median (95% confidence interval) cross sectional area of the upper airway increased by 18% (3 to 35) (p<0.02) in the hypopharynx and by 25% (11 to 69) (p<0.005) in the velopharynx, but not significantly in the oropharynx. Although in general the shape of the pharynx did not change following insertion of the oral appliance, the lateral diameter of the velopharynx increased to a greater extent than the anteroposterior diameter. Following insertion of the oral appliance the reduction in AHI was related to the increase in cross sectional area of the velopharynx (p = 0.01). CONCLUSIONS: A mandibular advancement oral appliance increases the cross sectional area of the upper airway during wakefulness, particularly in the velopharynx. Assuming this effect on upper airway calibre is not eliminated by sleep, mandibular advancement oral appliances may reduce the severity of obstructive sleep apnoea by maintaining patency of the velopharynx, particularly in its lateral dimension.